Comparison of Ionomic and Metabolites Response under Alkali Stress in Old and Young Leaves of Cotton (Gossypium hirsutum L.) Seedlings - Guo, Rui; Shi, LianXuan; Yang, ChunWu; Yan, ChangRong; Zhong, XiuLi; Liu, Qi; Xia, Xu; Li, HaoRu (Frontiers in Plant Science, 2016)
Soil salinization is an important agriculture-related environmental problem. Alkali stress and salt stress strongly influence the metabolic balance in plants. Salt and alkali stresses exert varied effects on old and young tissues, which display different adaptive strategies. In this study, we used cotton (Gossypium hirsutum L.) plants as experimental material to investigate whether alkali stress induces ionic and metabolism changes in old and young leaves of cotton plants exposed to alkali stress. Results showed that alkali stress exerted a considerably stronger growth inhibition on old leaves than on young leaves. Under alkali stress, young leaves can maintain low Na and high K contents and retain relatively stable tricarboxylic acid cycle, resulting in greater accumulation of photosynthetic metabolites. In terms of metabolic response, the young and old leaves clearly displayed different mechanisms of osmotic regulation. The amounts of inositol and mannose significantly increased in both old and young leaves of cotton exposed to alkali stress, and the extent of increase was higher in young leaves than in old leaves. In old leaves, synthesis of amino acids, such as GABA, valine, and serine, was dramatically enhanced, and this phenomenon is favorable for osmotic adjustment and membrane stability. Organs at different developmental stages possibly display different mechanisms of metabolic regulation under stress condition. Thus, we propose that future investigations on alkali stress should use more organs obtained at different developmental stages.